The psychological costs of war: Military combat and mental health - Resul Cesur; Joseph J. Sabia; Erdal Tekin (Institute for the Study of Labor (IZA), 2011)
While descriptive evidence suggests that deployment in the Global War on Terrorism is associated with adverse mental health, the causal effect of combat is not well established. Using data drawn from the National Longitudinal Study of Adolescent Health, we exploit exogenous variation in deployment assignment and find that soldiers deployed to combat zones where they engage in frequent enemy firefight or witness allied or civilian deaths are at substantially increased risk for suicidal ideation, psychological counseling, and post-traumatic stress disorder (PTSD). Our estimates imply lower-bound health care costs of 1.5 to 2.7 billion for combat-induced PTSD.
urn:nbn:de:101:1-201104134564
Keywords: H56; I1; 330; military service; post-traumatic stress disorder; depression; Krieg; Kriegsfolgen; Psychische Störung; Kosten; USA